(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2023)
Image-guided interventional procedures have become one of the medical applications that produces the highest doses of radiation for both the patient and the personnel involved in it. Safety assessment was applied to a generic service where image-guided interventional procedures was carried, using the semi-quantitative method of risk matrix, implemented in the Cuban SECURE-MR-FMEA code. The process map was prepared, identifying 6 stages with 76 accidental sequences. Values showed that the first screening for the developed model reports 45 % of high risks, 42% and 13 % of moderate and low risks, and once the number of controllers increased, high risks decrease to 11 % and there is an increase in moderate and low risks of 54 % and 35 % respectively. These results stress the importance of using all necessary measures for the protection of the public, patients and occupationally exposed workers.